Unveiling Power Relations: A Comparative Analysis of Individual and Group Influence in Wish (2023) Movie - Harahap, Gabriella Victoria Sabatini Theresia; Simbolon, Grita Meiske Hasianna; Pasaribu Habeahan, Jordan Agave McKenzie; Brasco, Putra Pratama Immanuel; Varen Raist (Jurnal Pendidikan Makarios, 2025)
This study analyzes the representation of individual and collective power in Wish (2023) through qualitative thematic analysis, drawing on Thomas Hobbes’ theory of individual power and Michel Foucault’s concept of relational power. The findings reveal that: 1) the protagonist’s pursuit of autonomy reflects Hobbes’ notion of individual power; 2) the interconnection of magic and authority illustrates Foucault’s link between knowledge and power; and 3) the narrative highlights resistance to domination at both personal and societal levels. The film demonstrates how cinematic texts critique power structures, offering insights into authority, resistance, and collective agency in contemporary contexts.